Radiocesium concentrations in shallow water sediments (Matsukawa-ura Lagoon, Fukushima, Japan) from a compact NaI(Tl) scintillation spectrometer. (September 2021) - Higuchi, Ken; Arakawa, Hisayuki; Matsumoto, Akira; Narita, Kaoru; Morioka, Yoshiaki
Abstract: We collected continuous sedimentary 137 Cs concentration data from a shallow fishery ground (Matsukawa-ura Lagoon, Fukushima, Japan) in 2016 using a new compact underwater NaI(Tl) scintillation spectrometer and a quantitative technique. 137 Cs concentrations in sediments were low (approx. 40 Bq/kg DW) at the lagoon mouth and high (641.2 Bq/kg DW) at the head of the lagoon. Some areas of locally elevated 137 Cs concentrations (>500 Bq/kg DW) were also found. Highlights: A seabed radioactivity monitor (S-RAM) measured 137 Cs in shallow sea sediments. The S-RAM offers low count times (60 s) and rapid measurements. Concentrations of 137 Cs in Matsukawa-ura Lagoon were 40–641.2 Bq/kg DW. Isolated areas of high 137 Cs (>500 Bq/kg DW) were detected in the southern lagoon.